An Analysis of the Slogans of the Quota Movement 2024 in Bangladesh Using Speech Act Theory: A Pragmatic Perspective - Akter, Shorna; Abedin, Md Minhajul (Mother Language, 2025)
The study aims to analyze the use of speech acts in the slogans of Quota Movement 2024 in Bangladesh. Using Searl’s (1969) taxonomies of Speech Act Theory (SAT), the researchers analyzed the selected slogans following a qualitative approach from a pragmatic perspective. The findings show that all the illocutionary acts have been used in the concerned slogans. Also, the study has shown how the slogans of the Quota Movement 2024 in Bangladesh played a crucial role in driving the listeners from the micro level to the macro level based on the situation demand of an ultimate goal. Mother Language, 2024; 8(1-2): 174-195